A rare case of spontaneous thrombolysis in a patient with acute myocardial infarction with ST-segment elevation - Yu.G. Kyyak (Danylo Halytsky Lviv National Medical University, 2018)
In the pathogenesis of acute myocardial infarction an important role belongs to coronary sclerosis and coronary artery thrombosis. Endothelium plays an important role in a regulation of vascular tone, local inflammation, hemostasis, neovascularisation. An impairment of endothelial barrier function occurs after direct damage of endothelial cells as a result of an atherosclerotic plaque destabilization, injury, chronic inflammation or exposure to hazardous substances. Breakage of the endothelial surface causes an exposure of subendothelial collagen and triggers expression of adhesive proteins (e.g. tissue factor and von Willebrand factor) and decreases synthesis of prostacyclin and nitric oxide. In case of its damage and activation, thrombocytes adhere and aggregate to each other which leads to thrombosis and can cause an acute myocardial infarction.